Pengaruh Pergantian Auditor, Opini Audit dan Ukuran KAP terhadap Audit Report Lag - Veronika Loda; Maulana Malik Muhammad (UNIVERSITAS KALBIS, 2022)
This study aims to examine the effect of auditor turnover, audit opinion, and Kap size on audit report lag. The sample used in this study were companies listed on the Indonesia Stock Exchange for the 2017-2019 period with a population of 66 and a sample of 47 companies. The sample was carried out using purposive sampling method with data analysis method using panel data multiple regression method. The results of this study indicate that audit opinion has a negative effect on audit report lag. Meanwhile, auditor turnover and the size of the Public Accounting Firm have no effect on audit report lag